ANALISA MENGENAI PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI PERUSAHAAN - Dian Sudiantini; Destya Fitri Andini; Dhea Syifa Khaerunisa; Dimas Listyanto Putra; Dinda Putri Armayani (Lafadz Jaya Publisher, 2023)
One of the success factors of a company is the existence of human resources in the form of competent employees to be able to produce good performance. However, to produce competent employee performance can be obtained through motivation and compensation. Employees receive compensation as a substitute for the remuneration they get from a company or organization. This study aims to analyze the company's compensation system for employee performance. With a qualitative approach, the research emphasizes the context of the problem under study. The author uses a type of qualitative research method with literature review journals. The authors use sources from Google Scholar, Perish or Publish, and other online media for all references in this study. The results of the study show that compensation has a positive impact on employees. Therefore, companies must pay attention to compensation to their employees to maintain the good performance of the employees themselves. This compensation can be in the form of financial and non-financial in the form of wages, benefits, social insurance, incentives, and convenient facilities.